A systematic review of the international published literature relating to quality of institutional care for people with longer term mental health problems - Caldas-de-Almeida, José M. (2017)
BMC Psychiatry Taylor, Tatiana L. Killaspy, Helen Wright, Christine Turton, Penny White, Sarah Kallert, Thomas W. Schuster, Mirjam Cervilla, Jorge A. Brangier, Paulette Raboch, Jiri Kalisova, Lucie Onchev, Georgi Dimitrov, Hristo Mezzina, Roberto Wolf, Kinou Wiersma, Durk Visser, Ellen Kiejna, Andrzej Piotrowski, Patryk Ploumpidis, Dimitri Gonidakis, Fragiskos Caldas-de-Almeida, Jose Cardoso, Graca King, Michael B.European Commission The authors would like to acknowledge all members of the international DEMoBinc Research Group and the project's funder, the European Commission. 138 BIOMED CENTRAL LTD LONDON 505SH